Temporomandibular disorder and anxiety, quality of sleep, and quality of life in nursing professionals - Larissa Kattiney OLIVEIRA; Guilherme de Araújo ALMEIDA; Éverton Ribeiro LELIS; Marcelo TAVARES; Alfredo Júlio FERNANDES NETO (Sociedade Brasileira de Pesquisa Odontológica, 2015)
To evaluate the association between temporomandibular disorder (TMD) and anxiety, quality of sleep, and quality of life in nursing professionals at theHospital de Clínicas de Uberlândiaof theUniversidade Federal de Uberlândia - HCU-UFU (Medical University Hospital of the Federal University of Uberlândia), four questionnaires were given to nursing professionals. The questionnaires were completed by 160 of these professionals. The Fonseca's questionnaire was used to evaluate the presence and severity of TMD, the IDATE was used to evaluate anxiety, the SAQ was used to evaluate quality of sleep, and the SF-36 was used to evaluate quality of life. Forty-one nurses (25.6%) reported having no TMD (Fonseca's questionnaire score ≤ 15), 66 (41.3%) had mild TMD (Fonseca's questionnaire score 20-40), 39 (24.4%) had moderate TMD (Fonseca's questionnaire score 45-65), and 14 (8.8%) had severe TMD (Fonseca's questionnaire score ≥ 70). According to Fonseca's questionnaire, the presence of TMD was associated with trait anxiety, but the TMD severity was associated with state anxiety classification (mild, moderate, severe). The SAQ score differed significantly from Fonseca classification. The Fonseca's questionnaire score correlated negatively with the score of each dimension of the SF-36 (r = -0.419 to -0.183). We conclude that TMD is common among nursing professionals; its presence was associated with trait anxiety, and its severity was associated with state anxiety. Hence, the presence of TMD may reduce quality of sleep and quality of life.